Robotic thymectomy: technical tips - Marulli, Giuseppe; Comacchio, Giovanni Maria; Rea, Federico (Video-Assisted Thoracic Surgery, 2017)
Thymectomy is the cornerstone in the treatment of thymic tumors and an accepted option for the multimodality management of myasthenia gravis (MG). Different surgical approaches have been described either open or minimally invasive. The introduction of robotic-assisted surgical systems has brought clear technical advantages over standard minimally invasive techniques. We present the surgical technique of robotic thymectomy that we apply for patients affected by myasthenia gravis and early stage thymoma.